Case Report: Antibodies to the N-Methyl-D-Aspartate Receptor in a Patient With Multiple Sclerosis - Zhou, Ran; Jiang, Fei; Cai, Haobing; Zeng, Qiuming; Yang, Huan (Frontiers in Immunology, 2021)
The association between multiple sclerosis and anti-N-Methyl-D-Aspartate receptor encephalitis is limited to merely a few case reports, and the exploration of the pathogenic mechanisms underlying the overlap of these two disease entities is very limited. Therefore, case reports and literature review on N-Methyl-D-aspartate receptor antibody in patients with multiple sclerosis are unusual and noteworthy. A young female had the first episode of paresthesia and motor symptoms with positive anti-N-Methyl-D-Aspartate receptor antibody and recovered after immunotherapy, and at the first relapse, the patient developed disorders of consciousness with positive anti-N-Methyl-D-Aspartate receptor antibody, findings of magnetic resonance imaging showed features of autoimmune encephalitis, which was also controlled by immunotherapy. At the second relapse, anti-N-Methyl-D-Aspartate receptor antibody turned negative while oligoclonal bands presented positive, and findings of magnetic resonance imaging showed features of multiple sclerosis. Afterwards, we followed the patient after receiving disease modifying treatment to monitor the efficacy and safety of teriflunomide. Based on literature review, demyelinating diseases patients with anti-neuronal antibody have complex, diverse and atypical symptoms, therefore, high attention and increased alertness are necessary for neurologists. Conclusively, anti-neuronal antibody may present in many neuroinflammatory conditions, and diagnostic criteria should be used with caution if the clinical presentation is atypical, and neurologists should not rely excessively on laboratory tests to diagnose neurological diseases. Timely and comprehensive examination and consideration as well as early standardized treatment are the key factors to reduce patient recurrence and obtain a good prognosis.